2002
DOI: 10.1111/j.1572-0241.2002.05614.x
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome of patients with active Crohn's disease exhibiting extensive and deep ulcerations at colonoscopy1

Abstract: Patients with CD exhibiting deep and extensive ulcerations at colonoscopy have a more aggressive clinical course with an increased rate of penetrating complications and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 26 publications
1
47
0
4
Order By: Relevance
“…Nevertheless, a few important studies in this field deserve further discussion (table 1). The first one is a monocentric retrospective study on 102 patients assessing the impact of endoscopic lesions at a unique but variable time point during the disease on the further risk of colonic resection [48]. In this study, the presence of deep ulcers covering more than 10% of at least 1 colonic segment was associated with a significant increase in the risk of colectomy at 3 and 8 years, when it exceeded 60%.…”
Section: Prediction Of Disease Evolution In CDmentioning
confidence: 91%
“…Nevertheless, a few important studies in this field deserve further discussion (table 1). The first one is a monocentric retrospective study on 102 patients assessing the impact of endoscopic lesions at a unique but variable time point during the disease on the further risk of colonic resection [48]. In this study, the presence of deep ulcers covering more than 10% of at least 1 colonic segment was associated with a significant increase in the risk of colectomy at 3 and 8 years, when it exceeded 60%.…”
Section: Prediction Of Disease Evolution In CDmentioning
confidence: 91%
“…Two studies have supplied important information. The prediction study by Allez [5] showed that the presence of severe endoscopic lesions in the colon, defined as deep colonic ulcers, predicted colonic resection with a risk ratio of 5.43 (95% confidence interval = 2.64–11.18). The population-based Frøslie study (IBSEN cohort) [6] showed that in UC and CD healing of the (ileo-)colonic mucosa results in better disease control and a decreased requirement of surgery (significant for UC at 5 years and for CD at 10 years).…”
Section: Risk Assessment For Outcome In the Ibd Patientmentioning
confidence: 99%
“…The simplified endoscopic severity score of CD has been widely used to grade mucosal inflammation [46]. In one study of a large adult population with CD, the presence of severe endoscopic lesions (defined as extensive and deep ulcerations of at least 10% of the mucosal surface of one segment of the ileocolon) was found to be significantly associated with progression to penetration and the eventual need for surgery [47]. This finding has not been corroborated in children where no formal studies using centralized reading of endoscopic photographs or videos has been completed in this population.…”
Section: Endoscopic Severitymentioning
confidence: 99%